Acupuncture Mechanism, Applications, and Future Development - Jiayao Qu (Wolters Kluwer Health/LWW, 2020)
Researches about ancient needling, technique, have been made for many decades, whereas the results are discrepant. People tried to use modern science to explore thoroughly about the real structure of acupuncture functions. Much more progress has been made than the last century. This review summarized some of the most prevailed theories about the mechanisms of acupuncture and their common applications. And lastly, this article discussed the future development for acupuncture.